A Companion to Medieval Pisa
1 online resource.
Keywords: Presenting medieval Pisa in a multidisciplinary study, A Companion to Medieval Pisa provides a comprehensive overview of the city at the time of its greatest fame and prosperity. The volume addresses central aspects of the city's history: its geomorphology and orientation towards the Mediterranean Sea; its ancient past; the archaeological basis for the study of the medieval city and its built environment; Pisa's urban and port infrastructure; its social organization and political and economic history; its cultural achievements in the visual and literary arts; and the legacy of the medieval past for the city today. Contributors are: David Abulafia, Monica Bini, Veronica Rossi, Stefano Bruni, Antonio Alberti, Gabriele Gattiglia, Alma Poloni, Giuseppe Petralia, Gabriella Garzella, Ewa Karwacka Codini, Cédric Quertier, Michele Campopiano, Michel Balard, Fabio Redi, Olimpia Vaccari, Mauro Ronzani, Maria Luisa Ceccarelli Lemut, Ottavio Banti, Marco Collareta, Karen Rose Mathews, Cristina Cagianelli, and Franco Cardini.